2005
DOI: 10.1037/0022-006x.73.1.116
|View full text |Cite
|
Sign up to set email alerts
|

Race Disparities in Psychiatric Rates in Emergency Departments.

Abstract: Psychiatric diagnoses based on the International Classification of Diseases--Ninth Revision were examined in the medical discharge records of 33,000 emergency department (ED) patients to determine if (a) psychiatric disorders were underdiagnosed, (b) there were race and gender disparities in psychiatric rates, and (c) psychiatric rates varied as a function of type of injury (e.g., self vs. other-inflicted injuries) and medical diagnosis. The observed psychiatric rate of 5.27% was far below the national prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 45 publications
3
21
1
Order By: Relevance
“…Demographic differences in BPD diagnoses in the earlier survey years showed lower rates among Black individuals, and Black males even more so, than among those in the White and Other NHDS race groups. This result echoes the similar discrepancies in diagnostic rates between racial groupings reported in adults (Kunen et al 2005,Neighbors et al 2003, and Strakowski et al 2003 and adolescents (Delbello et al 2001), but not previously reported among preadolescents. However, the latest three NHDS years show a steep increase in BPD discharges, especially for Black males.…”
Section: Discussioncontrasting
confidence: 48%
“…Demographic differences in BPD diagnoses in the earlier survey years showed lower rates among Black individuals, and Black males even more so, than among those in the White and Other NHDS race groups. This result echoes the similar discrepancies in diagnostic rates between racial groupings reported in adults (Kunen et al 2005,Neighbors et al 2003, and Strakowski et al 2003 and adolescents (Delbello et al 2001), but not previously reported among preadolescents. However, the latest three NHDS years show a steep increase in BPD discharges, especially for Black males.…”
Section: Discussioncontrasting
confidence: 48%
“…Richmond et al found that psychiatric comorbidity disorders were frequently found in individuals who presented to the ED with minor injuries (6). Others have found that psychiatric conditions are more oppressive for those of lower socioeconomic status (7,8). These studies show that an unplanned contact with the ED for treatment of a physical illness or injury should be viewed as an opportunity to identify undiagnosed psychiatric disorders.…”
Section: Introductionmentioning
confidence: 93%
“…Further, we hypothesized that individual clinical and demographic characteristics of consumers; such as age, gender, ethnicity, diagnosis, and prior history of service utilization, would also affect outcomes of care. More specifically, demographic variables, such as age, gender, and ethnicity, have been linked to differences in mental health status and service utilization (Carrington, 2006;Chow, Jaffee, & Snowden, 2003;Harris, Edlund, & Larson, 2005;Kunen, Niederhauser, Smith, Morris, & Marx, 2005;Snowden, 2005). Therefore, we expected that there would be differences in outcomes as a function of these variables; with women, older consumers, and ethnic minorities faring relatively worse than others.…”
Section: Introductionmentioning
confidence: 95%